Analyzing the Impact of Stock Market Fluctuations on Financial Strategies in the Sports Industry - Jiao Meng (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This paper explores the influence of stock market fluctuations on the financial strategies within the sports industry from 1998: Q1 to 2018: Q1. Utilizing advanced econometric techniques such as the Johansen co-integration test, vector error correction model, and Granger causality test, we analyze the interplay between stock market performance and financial decision-making in sports organizations. Our empirical research reveals that variations in stock prices can significantly impact the financial management practices of sports enterprises, particularly in terms of investment, funding, and sponsorship activities. The results indicate a long-term relationship between stock market behavior and financial strategy adaptations in the sports sector, with stock price volatility influencing the availability and demand for monetary resources within these organizations. The study highlights the need for sports financial managers to consider stock market trends as a critical factor in planning and forecasting, suggesting that fluctuations in stock prices are a significant indicator of future economic conditions that could affect sports-related financial decisions. This awareness is crucial not only for anticipating changes in operational funding and sponsorship engagements but also for strategic planning to safeguard the financial health of sports organizations against economic downturns.